Penerimaan Khalayak Terhadap Tayangan Infotainment Tentang Fenomena Artis Lepas Jilbab (Studi Pada Mahasiswi Muslimah di Malang Berdasarkan Kelompok Sosial) - Winda Hardyanti (ARISTO, 2019)
The phenomenon of the artist off the Veil in some time ther last became a topic of conversation in the media, was no exception in the television media. One of celebrity in Indonesia, Rina Nose, suddenly took off the veil she has been wearing the last few years. Impressions of infotainment offers the meaning that action ther is Nose Rina action is sad or concern. Based on these problems, researchers want to find out what kind of audience acceptance against the related phenomenon of infotainment news footage off the headscarf artist Rina Nose.  There are a lot of messages that are displayed through related cases Rina infotainment news Nose. Number of messages cannot be removed from the question of the multiplicity of viewpoints used media. The message has more than one potential readings. Through ther study researchers will be able to find out where the audience has a dominant hegemonic position, negotiated reading and oposisional, where the designation cannot be separated from the background to the life of each subject research. This research uses the research methods analysis of reception using the qualitative approach with in-depth interview data collection techniques. Ther research is expected to be able to give a new perspective on development-related issues of the current mass media through a scientific approach. Impressions of infotainment construct women who take off Jilbab with negative construction.  The results of ther research are found subject CP (veiled non cottage) and BN (veiled-off veil-veiled again) belonging to the dominant hegemonic subject reading, DR. (not veiled) included in the oppositional reading and IM subjects (off the veil) including negotiated reading for refusing. Decisions they refuse/accept/agree/disagree against the concept of meaning offered by media influenced by their background educational background in religious families, the experience of living in a veiled and the influence of peer group them. Based on the results of the research it is known that audiences receive the concept of the artist off the Jilbab in a variety of types of acceptance. The subject that comes from a group of veiled non pondok pesantren and a subject that never had the experience of taking off the veil before masukd in the dominant hegemonic category is influenced by the background of religious education in a family that was good enough and too influenced by experiences/mistakes of her jilbab. While the subject of the entry in the category of oppositional reading are those who reject the concept of social group comes from the infotainment not veiled because he considered that her experiences during ther time is not a problem although not veiled Muslim women. While the subject of the entry category negotiated reading is a subject that includes Muslim social group but is experiencing the same phenomenon with artist Rina Nose. The subject was influenced by her background as a person who has the principle of free and tend to be liberal.